1984
DOI: 10.1007/bf00001843
|View full text |Cite
|
Sign up to set email alerts
|

Influence of acclimation temperature and season on acute temperature preference of adult mountain whitefish, Prosopium williamsoni

Abstract: SynopsisTemperatures preferred by four groups of adult mountain whitefish, Prosopium williarnsoni, collected in October before spawning, in December after spawning, in late winter, and in spring were determined in the laboratory in a horizontal gradient. Acute temperature preference based on fish tested soon after capture and final preferendum estimates were 12.8 and 17.7"C, respectively (pre-spawning), 9.6 and 11.9"C (post-spawning), 10.8 and 9.9"C (win'ter), and 16.4 and 16.3"C (spring). Seasonal influence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 24 publications
(24 reference statements)
1
4
0
Order By: Relevance
“…Another experiment exposing wild, subadult and adult mountain whitefish to different temperature regimes in the laboratory found their thermal preference ranged from 11.1 to 16.4°C when acclimated between 7 and 15°C (Ihnat & Bulkley, 1984). Partially supporting these experimental results, the large mountain whitefish we observed were rare in the warmer upstream reaches of CR8 through CR10 where maximum temperatures ranged from 16 to 19°C, while abundance peaked in the cooler reaches of CR3 through CR5 (maximum temperature ~14°C).…”
Section: Do Mountain Whitefish Track Environmental Conditions That supporting
confidence: 79%
“…Another experiment exposing wild, subadult and adult mountain whitefish to different temperature regimes in the laboratory found their thermal preference ranged from 11.1 to 16.4°C when acclimated between 7 and 15°C (Ihnat & Bulkley, 1984). Partially supporting these experimental results, the large mountain whitefish we observed were rare in the warmer upstream reaches of CR8 through CR10 where maximum temperatures ranged from 16 to 19°C, while abundance peaked in the cooler reaches of CR3 through CR5 (maximum temperature ~14°C).…”
Section: Do Mountain Whitefish Track Environmental Conditions That supporting
confidence: 79%
“…Generally, the fish that comprise these different assemblages have experimentally determined temperature tolerances that are consistent with the thermal niches inferred in the present study. Within the regional pool of species in the SSRB, those with published mean temperature preferences below 15°C (cutthroat trout, bull trout, mountain whitefish, and longnose sucker; Vigg & Koch, ; Jobling, ; Cherry & Cairns, ; Ihnat & Bulkley, ; Eaton & Scheller, ; Dickerson & Vinyard, ; Beitinger et al., ; BC MELP ; Dunham et al., ; Huff, Hubler, & Borisenko, ) were all found in the coldest headwater regions of the SSRB. Species with published mean temperature preferences above 18°C (yellow perch, sauger, walleye, lake sturgeon, northern pike, emerald shiner, spottail shiner, quillback, white sucker; Scott & Crossman, ; Jobling, ; Cherry & Cairns, ; Kellogg & Gift, ; Cincotta & Stauffer, ; US EPA ; Eaton & Scheller, ; Beitinger et al., ; Lester, Dextrase, Kushneriuk, Rawson, & Ryan, ; Amadio, Hubert, Johnson, Oberlie, & Dufek, ; Benson, Sutton, Elliott, & Meronek, ; Amadio, Hubert, Johnson, Oberlie, & Dufek, ; Wilson & Nagler, ) were all found in the warm lowland regions of the SSRB.…”
Section: Discussionmentioning
confidence: 98%
“…Red lines in the right panels indicate the temperatures associated with high turnover in each river (see Figure 3). Green lines in the right panels depict the hierarchical clustering of sites based on the dissimilarity of species assemblages (longer distance between sites along the lines indicates greater dissimilarity) Jobling, 1981;Cherry & Cairns, 1982;Ihnat & Bulkley, 1984;Eaton & Scheller, 1996;Dickerson & Vinyard, 1999;Beitinger et al, 2000;BC MELP 2001;Dunham et al, 2003a;Huff, Hubler, & Borisenko, 2005) were all found in the coldest headwater regions of the SSRB. Species with published mean temperature preferences above 18°C (yellow perch, sauger, walleye, lake sturgeon, northern pike, emerald shiner, spottail shiner, quillback, white sucker; Scott & Crossman, 1979;Jobling, 1981;Cherry & Cairns, 1982;Kellogg & Gift, 1983;Cincotta & Stauffer, 1984;US EPA 1995;Eaton & Scheller, 1996;Beitinger et al, 2000;Lester, Dextrase, Kushneriuk, Rawson, & Ryan, 2004;Amadio, Hubert, Johnson, Oberlie, & Dufek, 2005;Benson, Sutton, Elliott, & Meronek, 2005;Amadio, Hubert, Johnson, Oberlie, & Dufek, 2006;Wilson & Nagler, 2006) were all found in the warm lowland regions of the SSRB.…”
Section: Discussionmentioning
confidence: 99%
“…Whitefish and suckers were sampled for this study because both species are present in the Oldman River and they have different species-specific temperature optima. Whitefish represent a cold-water fish species with a maximum temperature tolerance of 23.1°C (Eaton and Scheller 1996) and a thermal preference range between 12.8°C to 17.7°C [upper temperature preference (UTP)] (Ihnat and Bulkley 1984). Suckers represent a cool-water species with a maximum temperature tolerance of 27.4°C (Eaton and Scheller 1996) and a thermal preference range of 18.3°C to 24°C (UTP) (Eaton et al 1995).…”
Section: Description Of Sampling Sites and Fish Speciesmentioning
confidence: 99%